The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/app.48190
|View full text |Cite
|
Sign up to set email alerts
|

Near room temperature dyeing of m‐aramid fabrics

Abstract: Due to their high crystallinity and inertness, the coloration of meta-aramid fiber has been widely confirmed to be difficult. Though substantial improvements have been achieved, the dyeing of this fiber still requires high temperature and long duration for good color strength and shade. In this article, grafting poly(acrylic acid), a polyelectrolyte, onto meta-aramind fibers followed by dyeing via conventional pad-dry-cure technique resulted in good dyeing and a decrease the dyeing time and temperature. Dyed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Azam et al (2019) had success in dyeing meta-aramid fibers with disperse dye by increasing the dyeing temperature and concentration of the swelling agent. Vu and Michielsen (2019) explored dyeing meta-aramid fibers with basic dyes at lower temperatures by grafting poly(acrylic acid) onto the surface of the meta-aramid fiber, creating readily available bonding sites for a basic dye. Kim et al (Kim and Choi, 2011) also reported success in dyeing meta-aramid fibers with basic dyes by experimenting with swelling agents and concentrations of added electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Azam et al (2019) had success in dyeing meta-aramid fibers with disperse dye by increasing the dyeing temperature and concentration of the swelling agent. Vu and Michielsen (2019) explored dyeing meta-aramid fibers with basic dyes at lower temperatures by grafting poly(acrylic acid) onto the surface of the meta-aramid fiber, creating readily available bonding sites for a basic dye. Kim et al (Kim and Choi, 2011) also reported success in dyeing meta-aramid fibers with basic dyes by experimenting with swelling agents and concentrations of added electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the color of woven aramid materials uses primarily solution dyeing methods, in which the coloring of the yarns in the woven or knit fabric is determined by adding colorant to the polymer dope at the time the aramid filament is produced, thereby limiting the color options for the fabrics and their use in potential new applications. Various surface modification methods have been attempted to improve the dyeing of aramids, including chemical treatments with strong acids [ 2 , 3 ] and auxiliary additives [ 4 ], physical approaches using UV/O 3 irradiation [ 5 ] or nonthermal plasma [ 6 ], and chemical grafting using poly(acrylic acid) [ 7 ] or a diblock copolymer derived from methacryloyloxy-ethyl-trimethylammonium chloride [ 8 ], which claimed improved dyeability with different types of dyes. Most of these methods focused on the surface modification of meta-aramids, and few reported successes in dyeing para-aramids [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aramid fibers have been widely used in advanced textiles, including bullet‐proof vests and helmets, spacesuits, firemen's turn‐out coats, flame‐retardant gloves, industrial protective clothing, and so on 7–10 . However, due to the numerous hydrogen bonds between amide groups in polymer chains, its crystallinity and glass transition temperature ( T g 270°C) are high, 8 resulting in the extremely poor dyeability of aramid textile and especially low light fastness of the dyed aramid by conventional dyeing techniques, 11–13 which greatly limits the scope of its practical application. Moreover, the variety of colors of aramid fabrics is much less available than other fabrics.…”
Section: Introductionmentioning
confidence: 99%